CONTRIBUTION OF SOCIAL INSTITUTIONS TO WOMEN'S EMPOWERMENT PROGRAMS THROUGH EDUCATION (CASE STUDY OF INDONESIAN TEACHERS' COLLEGES AND INDONESIAN LITERACY SCHOOLS) - Siti Napsiyah; Yulianti Yulianti; Nadya Kharima (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
For everyone, education is the most important prerequisite and constitutional right. It assists individuals in reducing inequality and plays an important role in human development, which impacts overall socio-economic growth. Improved health, nutritional status, economic growth, population reduction, weaker empowerment and society as a whole are all benefits of increased literacy and education. Women's empowerment is the foundation for achieving gender equality, which is characterized by individual responsibilities, rights, and opportunities that do not depend on their gender. Thus, it is very important for Social Institutions to contribute to providing empowerment activities through education for women. The purpose of this study is to see how the contribution made by social institutions, especially the Indonesian Teacher School and the Indonesian Literacy School program in implementing empowerment programs through educators for women. This research method uses a qualitative research method that is descriptive, a process in which the researcher describes this conceptual framework as resembling a repetitive process.  Then the researcher conducted interviews with beneficiaries and program managers. In addition, the researcher also reviewed published literature that focused on the relationship between education and women's empowerment.  The results of this study show that the Indonesian Teacher School and the Indonesian Literacy School program are empowerment programs that focus on education for teachers and public awareness of the importance of literacy which is dominated by women. The contributions made by the two programs are focused on the formation  of critical thinking, personal competence, social competence, and productive competence.  The competencies formed are very beneficial for beneficiaries to continue to be empowered.